Applying quranic contemplation in counseling - Tamin, Daris (COUNS-EDU: The International Journal of Counseling and Education, 2016)
The intent of this research project was to explore the use of Quranic contemplation practices in counseling. In Islamic terminology that mean Quranic contemplation known as Tadabbur Al-Quran. Referring to this objective, this research is on the continuum between basic research and applied research. The research method that has been applied mix method beetwen quantitative and qualitative approaches. Integrating the two methods were considered appropriate for pragmatism paradigm adopted in this research. Based on the results of the research found that: Quranic Contemplation in Counseling that applicable on four general phases, namely: Exploration, Reading Scripture, Developing, and Supplication. In particular, at each session consists of seven steps, namely: (1) build engagement counselee to open his/her heart to accept the Quran as a heart medicine, the instructions for the peace of mind and happiness in life; (2) exposing the problems of the counselee; (3) identify the norms adopted counselee; (4) guiding the counselee for contemplations with Quran in the order: recited, guiding understand the meaning of the verse, raised the focus on words related to the problem, the main message conveyed paragraph, reflecting the message of verses in everyday life; and expand the discussion; (5) made a commitment to change the behavior of current and future; (6) invited to join in the spiritual community; and (7) guided prayer.